2015
DOI: 10.1039/c5md00011d
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a defined secondary binding region on β-adrenoceptors and putative roles in ligand binding and drug design

Abstract: Putative roles of a secondary binding region shared among beta-adrenoceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…30 When designing bitopic ligands, both the orthosteric and the allosteric fragments need to be selected carefully and the linker must be optimized for the target with respect to its attachment point, length, composition, and flexibility. 12,13 Bitopic ligands can be designed as orthosteric (inverse) agonists or antagonists connected to either positive or negative allosteric modulators (PAMs or NAMs), in theory providing access to many regulatory options. However, it is difficult to predict the outcome for such ligands.…”
Section: ■ Bitopic Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 When designing bitopic ligands, both the orthosteric and the allosteric fragments need to be selected carefully and the linker must be optimized for the target with respect to its attachment point, length, composition, and flexibility. 12,13 Bitopic ligands can be designed as orthosteric (inverse) agonists or antagonists connected to either positive or negative allosteric modulators (PAMs or NAMs), in theory providing access to many regulatory options. However, it is difficult to predict the outcome for such ligands.…”
Section: ■ Bitopic Ligandsmentioning
confidence: 99%
“…They contain two distinct pharmacophores which are connected by a linker, thus allowing concomitant binding to the orthosteric and an allosteric binding site of the same receptor monomer. In addition to the benefit of inducing selectivity into the orthosteric ligand, bitopic ligands can provide advantages such as higher affinity, improved off-rates, etc., and can induce signaling bias (i.e., functional selectivity). , …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that allosteric ligands of the MOR show varying abilities to modulate the orthosteric ligand’s affinity, efficacy, or both. , Allosteric ligands bind to a site on the receptor, termed as allosteric binding site, that is distinct from the site that endogenous orthosteric ligands bind (orthosteric binding site). An allosteric ligand can act as a positive allosteric modulator (PAM) which enhances the affinity or efficacy of an orthosteric ligand, a negative allosteric modulator (NAM) which inhibits the intrinsic affinity or efficacy, or a silent allosteric modulator (SAM) which occupies the allosteric binding site and has no effect on the affinity or efficacy. In addition, bitopic (dual steric) ligands which bind to both the orthosteric and allosteric binding sites of a single receptor monomer have been shown to have higher affinity, increase or decrease intrinsic efficacy, improve off-rates and induce functional selectivity. ,,, Thus, bitopic compounds may combine the advantages of orthosteric and allosteric ligands and carry unique pharmacological properties, e.g., higher selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[128] Although bitopic ligands are comprised of a combination of an orthosteric and an allosteric part, nonetheless they convey unique pharmacological properties. [77,79,108,120,121,[128][129][130][131][132][133][134] Bitopic ligands are formed by connecting the aforementioned two distinct parts with a suitable linker moiety resulting in a single chemical entity, that interacts simultaneously with the orthosteric binding site and allosteric binding site (Scheme 7). [108] Thus, bitopic ligands are bifunctional ligands similarly to the bivalent ligands previously presented herein; while the latter are designed to bind in two binding sites belonging to two different receptors, the former are designed to bind in two binding sites within the same receptor.…”
Section: Bitopic Ligandsmentioning
confidence: 99%
“…The inclusion of both an orthosteric ligand and allosteric modulator have been demonstrated to achieve higher affinity and potency (via orthosteric ligand) and selectivity (via allosteric modulator), enhance off‐rates and decrease intrinsic efficacy [128] . Although bitopic ligands are comprised of a combination of an orthosteric and an allosteric part, nonetheless they convey unique pharmacological properties [77,79,108,120,121,128–134] . Bitopic ligands are formed by connecting the aforementioned two distinct parts with a suitable linker moiety resulting in a single chemical entity, that interacts simultaneously with the orthosteric binding site and allosteric binding site (Scheme 7).…”
Section: Bitopic Ligandsmentioning
confidence: 99%